АМИР ТЕМУР ВА ТЕМУРИЙЛАР ДАВРИДА АЁЛЛАРНИНГ ИЖТИМОИЙ МАВҚЕИ ТАРИХШУНОСЛИГИДАН - Абдуллаева, Я.; Абдуллаева, А. (SCIENCE and SOCIETY, 2017)
In this article some works devoted to value and the role of women in development of a society in the period of Amir Temur and the temurids.
Keywords: Amir Temur; temurids; princesses; women; education; upbringing